Probabilistic scenario planning in agriculture: balancing risks through data-driven forecasting - Steinke, Jonathan; Ortíz Crespo, Berta (2021)
Probabilistic scenario planning in agriculture is a procedure that uses available data and expert estimates to inform decision-making across the food system in a way that minimizes economic risk.